PENGERINGAN KAYU KARET (Hevea brasiliensis) DENGAN METODE RADIASI MATAHARI (GREEN HOUSE) - Wiwin Tyas Istikowati; Nur Afik Bagustiana; Budi Sutiya (Lambung Mangkurat University-Indonesia, 2020)
The aim of this study is to analyze the optimal drying time of rubber wood (Hevea brasiliensis) in direct drying in the sun and by a solar kiln (green house). This research is expected to provide information on optimal drying time on natural drying directly under sunlight (solar radiation) and with kiln (Green House) to prolong the utilization of wood and reduce the costs. The parameters tested in this study are water content, density, drying rate, shrinkage, and color change. The results on optimal drying of rubber wood at 6 weeks drying time either in drying under direct sunlight or solar kiln in the green house.